INCREASED DRIVING FORCE OF NATURAL PLANT FIBER EXTRACTION RESULTS BASED ON THE RESULTS OF THE DEVELOPMENT OF NATURAL FIBER EXTRACTORS - Azizi, Muhammad; Azharuddin, Azharuddin; Malik, Irawan; Fitri, Muhamad (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2024)
This research was motivated by the lack of utilization of wasted plant parts so that there were previous extractors that had been made but were still not optimal. This study itself aims to determine the effect of changes in the driving power of natural plant fiber extractors on the extracted fibers compared to previous extractors so that later the fiber produced can be used as the main material for making natural composites. In this study, the extractor is a tool used to extract plant fibers lining banana stems. The method used in this study is by developing the previous extractor, especially in the drive motor that used to use a DC motor and then replaced with a 5.5 HP gasoline motor, drum blade cap, tool transmission and water drain slide. After the development of the extractor was carried out, it continued with the initial data collection process with the loading method with an average banana stem layer length of 165.5 〖mm〗^2 and an average weight of 6.91 kg where the results can be used to determine the power of the drive motor used in this tool. The process of extracting plant fiber from banana stem layers to determine the influence of the quality and quantity of fiber produced after tool development. As a result, the time needed to extract plant fibers averaged 9.3 seconds compared to previous tools which averaged 37.6 seconds manually and 42.3 seconds with DC motors.